Fatal Peritoneal Migration of Strongylus edentatus in a Foal. (October 2019) - Gonzales-Viera, O.; Fritz, H.; Mete, A.
Summary: A 7-month-old female mixed breed foal with a 2-day history of recumbency and inability to open its mouth convulsed acutely and died and was submitted for necropsy examination. The foal was thin and large patches of haemorrhage were present throughout the peritoneal wall, the diaphragmatic surfaces and the retroperitoneum. Numerous nematode larvae were visible on the serosal surfaces and penetrated and embedded into the subserosa associated with the haemorrhages. The dorsal portion of the abdominal diaphragm had a partial tear and large numbers of nematodes were within the muscle fibres. Histologically, the larvae had a smooth cuticle, polymyarian/coelomyarian musculature and multinucleated intestinal cells, and were typically surrounded by haemorrhage, neutrophils, dense fibrovascular connective tissue and rare multinucleated giant cells. Parasitological examination identified the larvae as Strongylus edentatus based on the morphology of the buccal capsule. Additionally, there was severe muscle necrosis of the tongue and liver tissue analysis detected selenium deficiency. S. edentatus infections are uncommon in California, USA, and are typically non-lethal. In this case, the selenium deficiency may have led to immunosuppression, resulting in the hyperinfection with S. edentatus, and to the muscle damage and tear of the diaphragm. Although ivermectin treatment was indicated in the history, inadequate deworming or anthelmintic resistance may have played a role in the severity of infection. Graphical abstract: Image 1